Impact of Foreign Direct Investment (FDI) on unemployment rate in sub-Saharan African countries: Panel ARDL analysis (West African Journal on Sustainable Development, 2024)
In spite of the importance of foreign direct investment in employment creation, unemployment rate in Sub Saharan African is still on alarming rate. It is on this that this study seek to examined the impact of FDI on  unemployment rates in sub-Saharan Africa using new econometric techniques for PMG/ARDL for the period 2000–2021. Taking into account the influence of education, population and the inflation rate, the long-run effect of foreign direct investment (FDI) on the unemployment rate is statistically significant, suggesting that foreign direct investment has a significant relationship with unemployment in the selected sub-region.The error correction model coefficient is negative and significant in the specification, indicating that the short-run imbalance is corrected in the long-run. Given the significant role of foreign direct investment inflows in influencing the unemployment rate, we recommend that governments in this region should provide adequate policy and good environment that will attract FDI. Also, education authorities should be able to provide the type of education (Skill acquisition) that will fit in the industries.
Keywords: Unemployment; Foreign Direct Investment (FDI); sub-Saharan Africa; PMG/ARDL and Cointegration